Landscape and Health: Connecting Psychology, Aesthetics, and Philosophy through the Concept of Affordance - Menatti, Laura; Casado da Rocha, Antonio (Frontiers in Psychology, 2016)
In this paper we address a frontier topic in the humanities, namely how the cultural and natural construction that we call landscape affects well-being and health. Following an updated review of evidence-based literature in the fields of medicine, psychology and architecture, we propose a new theoretical framework called “processual landscape”, which is able to explain both the health-landscape and the medical agency-structure binomial pairs. We provide a two-fold analysis of landscape, from both the cultural and naturalist points of view: in order to take into account its relationship with health, the definition of landscape as a cultural product needs to be broadened through naturalization, grounding it in the scientific domain. Landscape cannot be distinguished from the ecological environment. For this reason, we naturalize the idea of landscape through the notion of affordance and Gibson’s ecological psychology. In doing so, we stress the role of agency in the theory of perception and the health-landscape relationship. Since it is the result of continuous and co-creational interaction between the cultural agent, the biological agent and the affordances offered to the landscape perceiver, the processual landscape is, in our opinion, the most comprehensive framework for explaining the health-landscape relationship. The consequences of our framework are not only theoretical, but ethical also: insofar as health is greatly affected by landscape, this construction represents something more than just part of our heritage or a place to be preserved for the aesthetic pleasure it provides. Rather, we can talk about the right to landscape as something intrinsically linked to the well-being of present and future generations.